TADABBUR BASMALAH DALAM PERSPEKTIF LINGUISTIK DAN IMPLIKASINYA DALAM KEHIDUPAN - Hanna, Anifa Rifka; Nurrohim, Ahmad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This article explains that the sentence Basmalah is a very familiar phrase for Muslims, but in daily practice, the habit of reading it is often neglected. In fact, basmalah has a deep spiritual meaning and is the opening of the first revelation in the Qur'an. In the context of fast-paced and distracting modern life, it is important to re-examine the value and meaning of basmalah as a form of relying on God as well as a spiritual foundation in daily activities. This research employs a library research method with a descriptive approach and critical analysis of relevant classical and contemporary literatura. The stages of this research consist of four main steps, namely: first, identifying and collecting relevant literature through keywords such as